Determinants of Thyrotoxic Cardiomyopathy Recovery. (8th September 2013) - Oliveros-Ruiz, Lucia; Vallejo, Maite; Diez Canseco, L. Fernando; Cárdenas, Manuel; Hermosillo, J. Antonio G.
Abstract : The purpose was to evaluate the effect of the disease duration prior to treatment, thyroid hormones level, or both on the reversibility of dilated cardiomyopathy. Between January 2006 and December 2010, a longitudinal study with a 6 months follow-up was carried on. One hundred and seventy patients with hyperthyroidism were referred to the cardiologist, and 127 had a 6 months followup after antithyroid treatment and were evaluated by echocardiography. Dilated cardiomyopathy reversibility criteria were established according to echocardiographic parameters. Complete reversibility existed when all parameters were met, partial reversibility when LVEF was ≥55% plus two or three other parameters, and no reversibility when LVEF was ≤55% regardless of other parameters. The results showed that echocardiography parameters related to the regression of myocardial mass were associated with a disease duration shorter than 10.38 months. This was the main predictive variable for reversal of dilated cardiomyopathy, followed by β -blocker treatment, and the last predictive variable was the serum level of free triiodothyronine. This study showed that the effect on the myocardium related to thyrotoxicosis was associated with the disease duration before treatment.